The Impact Of Early Point-Of-Care Ultrasound (POCUS) On The Diagnosis And Management Of Shock In The Emergency Department: A Systematic Review (The Review of Diabetic Studies, 2025)
BackgroundPoint-of-care ultrasound (POCUS) has emerged as a vital diagnostic and management tool for evaluating patients presenting with undifferentiated shock in emergency settings. This systematic review synthesizes empirical evidence on the effectiveness of early POCUS in improving diagnostic accuracy, guiding resuscitation, and influencing patient outcomes.MethodsFollowing PRISMA 2020 guidelines, ten studies published between 2004 and 2025 were reviewed, including randomized controlled trials and observational studies. Databases searched were PubMed, Scopus, Web of Science, Embase, and Google Scholar. The included studies evaluated POCUS use in adult patients with nontraumatic hypotension or shock, measuring its impact on diagnostic accuracy, treatment modification, and mortality.ResultsAcross studies, POCUS consistently improved diagnostic certainty, with accuracy gains between 25% and 45%. Diagnostic agreement with final diagnosis reached κ = 0.7–0.89. Between 24% and 50% of cases experienced management changes following POCUS. Although no consistent survival benefit was observed, resource utilization (e.g., CT imaging, mechanical ventilation) was reduced.ConclusionEarly POCUS significantly enhances diagnostic accuracy and clinical decision-making in patients with undifferentiated hypotension but shows no definitive survival advantage. Its integration into early shock evaluation protocols improves workflow efficiency and resource optimization in emergency departments.